Pharmacokinetics and pharmacodynamics of peptide antibiotics - Bian, Xingchen; Qu, Xingyi; Zhang, Jing; Nang, Sue C.; Bergen, Phillip J.; Tony. Zhou, Qi; Chan, Hak-Kim; Feng, Meiqing; Li, Jian (Advanced drug delivery reviews, 2022)
[Display omitted] •Antimicrobial peptide antibiotics are key therapeutic options for the treatment of multidrug-resistant infections.•Pharmacokinetics/Pharmacodynamics is essential to the rational use of antimicrobials.•Structural modifications of the antimicrobial peptide antibiotics can substantially alter their pharmacokinetics and pharmacodynamics.•Therapeutic drug monitoring is recommended for antimicrobial peptide antibiotics due to their relatively narrow therapeutic windows. Antimicrobial resistance is a major global health challenge. As few new efficacious antibiotics will become available in the near future, peptide antibiotics continue to be major therapeutic options for treating infections caused by multidrug-resistant pathogens. Rational use of antibiotics requires optimisation of the pharmacokinetics and pharmacodynamics for the treatment of different types of infections. Toxicodynamics must also be considered to improve the safety of antibiotic use and, where appropriate, to guide therapeutic drug monitoring. This review focuses on the pharmacokinetics/pharmacodynamics/toxicodynamics of peptide antibiotics against multidrug-resistant Gram-negative and Gram-positive pathogens. Optimising antibiotic exposure at the infection site is essential for improving their efficacy and minimising emergence of resistance.